2020
DOI: 10.1186/s12885-020-07569-8
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of BRF2 as a prognostic biomarker in invasive breast carcinoma

Abstract: Background Deregulation of the RNA polymerase III specific TFIIIB subunit BRF2 occurs in subtypes of human cancers. However, correlations between BRF2 alterations and clinical outcomes in breast cancer are limited. We conducted this review to analyze BRF2 alterations in genomic data sets housed in Oncomine and cBioPortal to identify potential correlations between BRF2 alterations and clinical outcomes. Methods The authors queried bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The size of BDP1 has hindered researchers from working on full-length BDP1 in vitro to the extent in vitro characterization has progressed on other TFIIIB subunits. Advances in microarray and RNA-sequencing have provided a more focused approach to studying TFIIIB activity in cancer, specifically with these analyses performed using clinical samples [ 6 , 25 , 34 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of BDP1 has hindered researchers from working on full-length BDP1 in vitro to the extent in vitro characterization has progressed on other TFIIIB subunits. Advances in microarray and RNA-sequencing have provided a more focused approach to studying TFIIIB activity in cancer, specifically with these analyses performed using clinical samples [ 6 , 25 , 34 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenes MAP kinase ERK and MYC [ 11 , 17 ] stimulate TFIIIB activity in vitro. The TFIIIB subunits TBP [ 18 , 19 , 20 ], BRF1 [ 21 , 22 , 23 , 24 ], and BRF2 [ 6 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have begun to be studied in specific human cancers. For example, BRF2 has been classified as a novel proto-oncogene in human cancers [ 6 , 27 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a publicly available cohort of 982 lung cancer patients, we found that low expression of ST3GAL5 was associated with a poor prognosis of survival until first progression (Fig 7I ; Gyorffy et al , 2013 ). In addition, analysis of the mRNA expression level of ST3GAL5 using the Oncomine database showed that ST3GAL5 is frequently expressed at low levels in various human cancer tissues, including lung cancer tissues, compared to the corresponding adjacent normal tissues (Fig EV5F ; Neapolitan et al , 2015 ; Cabarcas‐Petroski et al , 2020 ; Saha et al , 2020 ). This finding is consistent with the results obtained by analysis of the Bhattacharjee Lung database: low levels of ST3GAL5 were detected in lung cancer compared to adjacent normal tissues (Fig 7J ; Bhattacharjee et al , 2001 ; Granville & Dennis, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recruitment of the RNA Polymerase III relies on TFIIIB, a core transcription factor composed of three subunits: (i) TBP, (ii) Bdp1 [124], and (iii) Brf2 (Brelated factor 2). Recent studies have highlighted a direct link between Brf2 over-expression and many types of cancer, including lung [125,126] and breast cancer [127,128]. The crystal structure of Brf2 in complex with TBP and the DNA revealed the presence of a conserved cysteine interacting with DNA [121].…”
Section: Nrf2 Regulation and The Selenium Connectionmentioning
confidence: 99%